Exploration of Factors Affecting the Interest of SMK Negeri 1 Binjai Students to Continue Their Studies to Higher Education - Loise Arinandha Br Sinulingga; Erwita Ika Violina; Fadinda Aisyah (Era Scientific Publisher, 2026)
The decision to pursue higher education is a critical educational transition for vocational high school students and is influenced by a complex interplay of personal and environmental factors. Despite the growing importance of higher education in enhancing career opportunities and social mobility, relatively limited research has qualitatively explored the factors shaping vocational students’ aspirations to continue their studies. Therefore, this study aimed to explore the internal and external factors influencing the interest of twelfth-grade students at SMK Negeri 1 Binjai in pursuing higher education. This study employed a qualitative descriptive approach with an exploratory design. Ten twelfth-grade students from the Accounting and Financial Institution (AKL) program were purposively selected based on recommendations from the school guidance and counseling teacher. Data were collected through semi-structured interviews, observations, and document analysis. The data were analyzed using the interactive model of Miles and Huberman, which includes data condensation, data display, and conclusion drawing. The trustworthiness of the findings was enhanced through source and technique triangulation. The findings revealed that students’ interest in pursuing higher education is shaped by both internal and external factors. Internal factors included motivation, career aspirations, educational awareness, field-of-study interests, and future planning, while external factors comprised family support, school and guidance counseling services, peer influence, economic conditions, and access to information about higher education. Among these factors, motivation and career aspirations emerged as the strongest drivers of students’ educational aspirations, whereas financial constraints represented the primary barrier to higher education participation. Family support and school-based guidance services were found to play significant roles in strengthening students’ intentions to continue their studies. This study contributes to the literature on career guidance and educational decision-making by providing an in-depth understanding of vocational students’ higher education aspirations. The findings highlight the importance of comprehensive career guidance programs, family involvement, and financial support mechanisms in promoting higher education participation among vocational high school students.